Implementation of Differentiated Learning in Independent Curriculum in Indonesian Language - Miswati Miswati; Fatma Yarni; Lestari Ramadhani (CV Berkah Syahdin Trust, 2025)
This research starts from the problems in the field, namely the implementation of differentiated learning in the newly implemented and applied independent curriculum so that many schools have not been able to implement this differentiated learning. This study aims to see how the implementation of differentiated learning in the independent curriculum in the Indonesian language subject at MIN 3 Tanah Datar, which consists of planning, implementation, and evaluation of learning. The type of research that the author uses is a qualitative research type with a qualitative descriptive method on the research subjects in the field. The data collection techniques used are through observation, interview, and documentation techniques. Data processing is carried out qualitatively descriptively, then described based on the problems that occur in the field using effective sentences. The data sources for this study are class 1 teachers, representatives of the Min 3 Tanah Datar curriculum and students. The data analysis techniques used are data reduction, data presentation (data display) and drawing conclusions. The data validity assurance technique used is triangulation of sources, techniques and time. Based on the research conducted, it is known that teachers carry out differentiated learning planning in the independent curriculum by compiling teaching modules with student needs analysis, identifying the dimensions of the Pancasila profile, determining core competencies, compiling teaching materials, compiling learning implementation, and compiling learning evaluations. Then the teacher carries out the implementation of differentiated learning which consists of 3 aspects, namely content differentiation, products, and processes. There are three evaluations in the differentiated learning process carried out by teachers, namely diagnostic assessment, formative assessment, and summative assessment.